Students’ Trends in Islamic Communication Postgraduate in 2010-2016 State Islamic University of North Sumatera (UINSU) - Anang Anas Azhar; Ahmad Tamrin Sikumbang (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
This article aims to discuss the tendency of specialization of students of the Islamic communication study program at the Postgraduate Program of the State University of North Sumatra in 2010-2016, mapping the various kinds of tendencies and interests of UINSU Islamic communication and broadcasting students. By looking at various trends of interest that exist. All of them were obtained from observations of students and graduation of UINSU Islamic broadcasting communication. This research relies on field study methods and library research, conducted at the Islamic University of North Sumatra (UINSU). The data found from the study of academics include: 1.) As an implication of the tendency of students who have graduated from the undergraduate education program to the postgraduate level to choose the same study program as in the Islamic communication and broadcasting study program at UIN North Sumatra, then that also along with the high numbers that affect the motivation of strata 1 to return to study and continue their education at a higher level. This condition is caused by learning motivation can grow because of the need for what is learned, both for the present and the future. That someone who has intrinsic motivation always wants to advance in learning. This desire is motivated by positive thinking, that everything learned at the strata-level will be needed and very useful now and in the future. 2.) The interest of the community is increasing to choose the Islamic broadcasting communication department as the chosen study program to continue the study, considering that the administrative conditions are relatively easy and do not make students who continue their studies happy and fast in completing their studies, it does not mean that the graduates with the state of administration and graduates graduating on time.